(3GdaUhd GdegeI aj eYQaI GdCFeIs - (3Ydj Hf eMeO Hf CMeO, fhQ GdOjf GHf GdUHGZ,J (B855 (3g` s
(3ChdgG (B:s
(3hHYO aYf di Cf CPcQ ai gPG GdcJGH aUhdG egeg ai eYQaI GdCFeI s
(3BNQgG (B:s
(3GfJgi Pdc hGddg GYde s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B8 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B178s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B175 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B227 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs